Rare presentation of a localised malignant pleural mesothelioma with cranial metastasis. (4th October 2016) - Ertan, Gulhan; Eren, Abdulkadir; Ulus, Sila
Abstract : Mesothelioma is an uncommon malignant neoplasm and a localised form of the pleura is especially very rare. Diagnosis of localised malignant pleural mesothelioma (LMPM) is very challenging. Histopathological verification is the gold standard, and studies such as CT, positron emission tomography (PET) and thoracoscopy are very valuable tools in assisting diagnosis. We report a case of histopathologically proven LMPM, which was discovered as a well circumscribed solitary subpleural nodule on PET-CT after presentation with cranial metastasis. This case shows that LMPM can present with uncommon radiological and clinical appearances, and imaging tools such as PET-CT have a very important role in diagnosis.